Myocellular basis for tapering in competitive distance runners - Luden, N.; Hayes, E.; Galpin, A.; Minchev, K.; Jemiolo, B.; Raue, U.; Trappe, T. A.; Harber, M. P.; Bowers, T.; Trappe, S. (Journal of Applied Physiology, 2010)
The purpose of this study was to examine the effects of a 3-wk taper on the physiology of competitive distance runners. We studied seven collegiate distance runners (20 ± 1 yr, 66 ± 1 kg) before and after a 3-wk taper. The primary measures included 8-km cross-country race performance, gastrocnemius single muscle fiber size and function (peak force, shortening velocity, and power), baseline and exercise-induced gene expression 4 h after a standardized 8-km run, citrate synthase activity, and maximal and submaximal cardiovascular physiology (oxygen consumption, ventilation, heart rate, and respiratory exchange ratio). Race performance improved by 3% following taper (P < 0.05). Myosin heavy chain (MHC) IIa fiber diameter (+7%, P < 0.05), peak force (+11%, P = 0.06), and absolute power (+9%, P < 0.05) increased following taper. In addition to the MHC IIa adaptations, taper elicited a distinct postexercise gene response. Specifically, the induction of MuRF-1 was attenuated following taper, whereas MRF4, HSP 72, and MT-2A displayed an exaggerated response (P < 0.05). No changes were observed in MHC I size or function, baseline gene expression, citrate synthase activity, or cardiovascular function. Our findings show that tapered training in competitive runners promoted MHC IIa fiber remodeling and an altered transcriptional response following the same exercise perturbation, with no adverse affects on aerobic fitness. Together, these results provide a myocellular basis for distance runners to taper in preparation for peak performance.